2015
DOI: 10.5505/tjtes.2015.56798
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intracorporeal Knotting and Endoloop for Stump Closure in Laparoscopic Appendectomy

Abstract: BACKGROUND: Several appendiceal stump closure tecniques such as intracorporoeal-knotting, endoloop, stapler and clips are used during laparoscopic appendectomy. This study aimed to compare intracorporoeal-knotting and endoloop tecniques used to close appendiceal stump in laparoscopic appendectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
(26 reference statements)
2
14
0
Order By: Relevance
“…In their study comparing single proximal endoloop and Hem-o-lock clips, Lucchi et al [12] found that patients in both groups experienced a similar length of hospital stay and the rate of infectious complications. Bali et al [16] compared the use of double intracorporeal knots and endoloops and found that the duration of operation was higher when the intracorporeal knot was used, but there was no difference in the rate of complications. In the study by Rossem et al [11] comparing the use of double proximal endoloops and endostaplers, no significant difference was observed between the two groups about duration of operation and infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…In their study comparing single proximal endoloop and Hem-o-lock clips, Lucchi et al [12] found that patients in both groups experienced a similar length of hospital stay and the rate of infectious complications. Bali et al [16] compared the use of double intracorporeal knots and endoloops and found that the duration of operation was higher when the intracorporeal knot was used, but there was no difference in the rate of complications. In the study by Rossem et al [11] comparing the use of double proximal endoloops and endostaplers, no significant difference was observed between the two groups about duration of operation and infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…There is no difference in polymeric clips safety and complications in comparison with other techniques such as endo stapler, endo loop or suture knot (4,7,10,14,18,22). But it should be avoided in gangrened appendiceal base or wide base more than 10 mm.…”
Section: Metallic Clips 5 -20mentioning
confidence: 99%
“…Laparoscopic appendectomy (LA) was done by Semm in 1983 for the first time and nowadays, it is the choice and maybe the gold standard procedure in the presence of an experienced surgeon (2-6) LA especially is preferred in female, obese and old patients (2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations